2022
DOI: 10.31234/osf.io/ef23g
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of acute stress on dishonesty: the moderating role of moral default

Abstract: Life abounds with situations in which we must decide whether to act unethically for personal gain or to be prosocial, thus maintaining a positive image of ourselves as being a ‘good person’. Evidence suggests that acute stress may influence moral decisions and prosocial behavior. However, it is currently unclear whether stress increases or decreases immoral behavior. Here, we hypothesize that stress, through its effects on cognitive control, has different effects on moral decision making for different individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
(53 reference statements)
0
5
0
Order By: Relevance
“… Schulreich et al, 2022 ). Thus, an exciting avenue for future work would be to determine whether acute stress exacerbates existing differences in impulsivity and impatience in delay discounting tasks ( Speer et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“… Schulreich et al, 2022 ). Thus, an exciting avenue for future work would be to determine whether acute stress exacerbates existing differences in impulsivity and impatience in delay discounting tasks ( Speer et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not yet clear when acute stress accentuates or supresses existing prosocial tendencies. For example, Schulreich et al (2022) found that increases in cortisol were associated with reductions in donations in participants scoring high on mentalising, whereas Azulay et al (2022) found that that increases in cortisol predicted enhanced donations in participants with high trait empathy (see also 32). Given the heterogeneity in behaviour in economic games under stress (7), future studies may benefit from manipulating the effort involved in helping, or other non-financial costs, to help us understand how the social behaviour of different individuals is affected by acute stress.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Speer et al (32) showed that acute stress can accentuate existing differences in dishonesty (cf. 33,34).…”
Section: Introductionmentioning
confidence: 92%
“…Similarly, Speer et al (Speer et al, 2022) showed that acute stress can accentuate existing differences in dishonesty (cf. Schulreich et al, 2022;Ying et al, 2022).…”
Section: Introductionmentioning
confidence: 92%
“…However, it is not yet clear when acute stress accentuates or supresses existing prosocial tendencies. For example, Schulreich et al (2022) found that increases in cortisol were associated with reductions in donations in participants scoring high on mentalising, whereas Azulay et al (2022) found that increases in cortisol predicted enhanced donations in participants with high trait empathy (see also Speer et al, 2022). Given the heterogeneity in behaviour in economic games under stress (Nitschke, Forbes, et al, 2022), future studies may benefit from manipulating the effort involved in helping, or other nonfinancial costs, to help us understand how the social behaviour of different individuals is affected by acute stress.…”
Section: Individual Differences In Prosocial Traits As Measured By So...mentioning
confidence: 99%